Process Tracing Innovations in Practice: Finding the Middle Path - Aston, Thomas; Wadeson, Alix (Institute of Development Studies, 2023)
Evaluation practitioners in the international development sector have given considerable attention in recent years to process tracing as a m ethod for evaluating impact, including discussion of how to assess the relative importance of causal factors. Despite the increasing interes t, there is a relative dearth of examples of practical learning and ev idence of applying process tracing in practice. This CDI Practice Pape r draws on comparative learning from applying three different types of process tracing in international development initiatives. It argues i n favour of a ‘middle path’ of applying evidence tests and rubrics to structure evaluative judgements rather than formal Bayesian updating o r looser forms of process tracing. It also calls attention to the pote ntial added value of taking a participatory approach, offering practic al recommendations for how to do this effectively.